Sildenafil Treatment of Primary Pulmonary Hypertension - Kevin B Laupland; Doug Helmersen; David A Zygun; Sidney M Viner (Canadian Respiratory Journal)
A 37-year-old woman with primary pulmonary hypertension and worsening symptomatology underwent pulmonary artery (PA) catheterization and vasodilator trials. Oxygen had no effect, but 10 parts/million of nitric oxide reduced mean PA (PAm) pressure by 20%. Prostacyclin infusion at 8 ng/kg/min decreased the PAm pressure by 11%, but further dose increases were limited by systemic hypotension. Sildenafil in doses of 25 mg or higher resulted in an average decrease of 14% in PAm pressure. Sildenafil is a potentially useful treatment option for patients with primary pulmonary hypertension, and further investigation is warranted.